Business Development Strategy for Bunga Melati Women’s Farming Groups in Bunutin Village, Bangli District, Bangli Regency - Putu Zanes Costalina Ge’i; Ni Wayan Sri Astiti; Putu Udayani Wijayanti (Journal of Sustainable Development Science, 2024)
This research aims to find out the right strategy for business development of the Bunga Melati Women's Farming Group (WFG) in Bangli Regency. The data collection method uses observation, interviews, documentation and Focus Group Discussion (FGD). The respondents in this research were all members of the Jasmine Flower Farming Women's Group, totaling 28 people. The data analysis used in this research is internal and external environmental analysis. The research results show that Bunga Melati WFG has a total IFAS score of 2.87, and an IFAS score of 2.87. The alternative strategy produced by Bunga Melati WFG is 1. Utilizing product diversity and superior quality to expand the scope of product promotion and branding. 2. Study new technological developments to improve efficiency and product quality. 3. Improving the quality of human resources through training and education programs to understand business administration management and also online marketing supported by new technology. 4. Strategy for using digital technology to increase product promotion and branding. 5. Improve product quality to face tight competition and high consumer bargaining power. 6. Product quality-based differentiation strategy by controlling product costs to increase consumer purchasing power. 7. Strategy for understanding customer needs in order to improve product quality. 8. Strategy for developing human resources and increasing competitiveness amidst intense competition and high consumer bargaining positions.